Do stock markets comove in emerging economies? - (:unkn) unknown (IGI Global, 2017)
Great Recession has brought the need to model and assess the financial markets with unconventional approaches. The nature of consumer behavior in financial markets has become crucial as real and financial sector comoving overtime was a dream of no rationality. The union of consumers looking for higher wealth and speculative stock market participants was not a sustainable case. But, what happened to the consumers/investors in emerging economies? This chapter assesses the behavior of emerging stock markets during the turmoil using weekly data for Brazil, China, India, Indonesia, Russia, South Africa and Turkey with US as the benchmark for January 2003-March 2014. Two unconventional methods are used for checking asymmetric contagion; the wavelet comovement and frequency domain causality. The findings show that markets with rather high concentration of foreign investors are highly affected but consumers were not due to smaller participation. The asymmetric contagion argument is verified for some emerging markets as consumers/investors suffered as much as any other market participant. © 2017 by IGI Global. All rights reserved.